2012
DOI: 10.5402/2012/268159
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Fruit-Feeding Butterflies (Lepidoptera, Nymphalidae) in a Brazilian Semiarid Area

Abstract: A survey of 6,000 trap/hours using fruit-bait traps was conducted, in order to characterize the community of fruit-feeding butterflies and their seasonal variation in a semiarid area of NE Brazil, which exhibits a highly seasonal rainfall regime. The community was composed of 15 species, the four most abundant comprising more than 80% of the total individuals. In the first sampling month, 80% of the species had already been recorded. A strong positive correlation was found between butterfly abundance and preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 21 publications
4
23
3
3
Order By: Relevance
“…This pattern is different from that of the Caatinga Biome (Nobre et al 2012), in which these subfamilies accounted for 41% of all butterfly individuals captured, and Charaxinae as the most abundant subfamily accounted for 57% of all captures. Dissimilarities regarding the climate and the habitat structure of both biomes can help explain the differences.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…This pattern is different from that of the Caatinga Biome (Nobre et al 2012), in which these subfamilies accounted for 41% of all butterfly individuals captured, and Charaxinae as the most abundant subfamily accounted for 57% of all captures. Dissimilarities regarding the climate and the habitat structure of both biomes can help explain the differences.…”
Section: Discussioncontrasting
confidence: 92%
“…More abundant species benefit from the wet season and grow in number until the T.wd. In this way, the response of the most abundant species could be associated with Previous studies have reported that forested habitat has great temporal species turnover, suggesting that habitat structure is an important factor in the temporal dynamics of butterflies (Shahabuddin & Terborgh 1999;Hamer et al 2005;Barlow et al 2008;DeVries et al 2011;Nobre et al 2012). The results of the present study agree with this hypothesis and indicate that the open habitat surveyed (i.e., savanna), in contrast to the forested habitat surveyed, is spatially less diverse and, as a consequence, has a butterfly assemblage that is more homogeneously distributed over the seasons (Hamer & Hill 2000;Hamer et al 2003).…”
Section: Figmentioning
confidence: 87%
“…A similar pattern occurs in seasonal deciduous forest, where the greatest abundance of butterflies in open areas occurs due to the great abundance of the butterflies adapted to the strong solar exposure. However, rupestrian grasslands are characterized by high temperatures during the dry season, when this positive relation no longer occurs [17]. A great density of habitat generalist species in small fragments reflects the nature of the surrounding landscape [80].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, natural areas exhibit larger fluctuations in water availability, with increased production of plant foliage biomass during wet seasons promoting growth and survival of larval stages (Aide 1992). However, this simplistic pattern is not always adhered to because of unpredictable weather variations that alter the timing and manner in which plants modify their foliage, so spillovers can occur where there are delays in ovipositing and/or adults eclosing (Nobre et al 2012). Where the decreases in butterfly abundance were evident in our study (e.g., at the beginning of the second dry season/August in Skeldon and LBI secondary forests), it is likely that conditions were not suitable for the adult forms so catch numbers were low.…”
Section: Discussionmentioning
confidence: 99%